Cool green : amazing, remarkable trees - Delacre, Lulu (Candlewick Press, 2023)
"As he works with his young granddaughter to nurture a potted sapling, a Latino landscaper shares his love and admiration of trees. From the extraordinary rainbow gum tree to the mighty, towering redwood, each of the thirteen specimens he tells of is a miracle of the natural world--and some are strange beyond the wildest imagining. Brimming with exuberance and color, this ode to trees of the world--and the vast knowledge of landscapers and gardeners--offers a feast for the eyes, with author-illustrator Lulu Delacre paying touching tribute by imbedding seeds, fronds, and leaves within her art. Complete with an author's note, glossary, and further information on the featured trees, Cool Green will have readers eager to turn the pages to discover each new reminder of what a precious place our earth is."--